Templating as a Strategy for Translating Official Documents from Spanish to English - Lambert-Tierrafría, Sylvie (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThis article examines the case of translation of official documents from Spanish into English in Canada. The article begins by providing some background information about immigration in Canada and in the Ottawa region in particular, and discussing the impact that this is having on translation needs. It then describes the types of official documents that need to be translated (e.g., birth, death, marriage certificates). Next, a type of translation tool known as a Translation Memory is briefly introduced, followed by an explanation of why, contrary to expectations, such a tool is not necessarily suitable for translating official documents. Finally, an alternative strategy that entails the creation and application of templates is presented. This templating approach is being developed and taught in Spanish translation courses at the University of Ottawa in Canada.